2014
DOI: 10.1007/s00381-014-2534-0
|View full text |Cite
|
Sign up to set email alerts
|

Placement of subdural grids in pediatric patients: technique and results

Abstract: Invasive subdural recordings are a safe and efficacious tool to identify the epileptogenic zone and its relationship to functional cortex in highly selected patients with medically refractory epilepsy. The ability to localize the EZ approaches 90 to 100 %, but seizure-free outcome is more complex depending greatly on the experience of the surgical team and the extent of resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Intracranial EEG (IEEG) is a clinical procedure in which electrical activity is sampled directly from the cortex with relatively high spatial and temporal resolution . Although IEEG recordings are traditionally assessed by visual inspection, recent advances in computing power and automated IEEG techniques have allowed researchers to study cortical synchronization across visually inaccessible spatiotemporal scales.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intracranial EEG (IEEG) is a clinical procedure in which electrical activity is sampled directly from the cortex with relatively high spatial and temporal resolution . Although IEEG recordings are traditionally assessed by visual inspection, recent advances in computing power and automated IEEG techniques have allowed researchers to study cortical synchronization across visually inaccessible spatiotemporal scales.…”
mentioning
confidence: 99%
“…9 Intracranial EEG (IEEG) is a clinical procedure in which electrical activity is sampled directly from the cortex with relatively high spatial and temporal resolution. 10 Although IEEG recordings are traditionally assessed by visual inspection, recent advances in computing power and automated IEEG techniques have allowed researchers to study cortical synchronization across visually inaccessible spatiotemporal scales. At the global (i.e., multi-electrode) scale, functional connectivity encodes the statistical similarity of electrical events between all pairs of electrodes, thereby measuring synchronized activity across distributed cortical networks.…”
mentioning
confidence: 99%
“…The advantages to grid placement include dense electrode coverage in the absence of a structural lesion identified by MRI, resolution of discordant noninvasive testing, evaluating the relationship of a structural lesion to an epileptic zone, evaluation of patients with dual pathology or multifocal epilepsy, and extraoperative awake cortical stimulation mapping to identify primary cortex and map eloquent function (49). The risks of staged craniotomy and placing large electrode arrays include intracranial hemorrhage, compression of cortical vascular structures causing cerebral edema and ischemia, as well as cerebrospinal fluid leak and meningitis.…”
Section: Intracranial Electroencephalography (Eeg)mentioning
confidence: 99%
“…Modern-day SDEs are manufactured as thin rows (i.e., strips) or flexible sheets (i.e., grids) of small stainless steel or platinum electrode contacts. 22 The implantation of SDEs typically requires larger cranial openings, either via a burr hole (for strips) or a generous craniotomy (for grids), through which they are applied directly to the cortical surface. 23 In some cases, a small number of intracerebral "depth" electrodes are added to complement the sampling of a deep focus of gray matter.…”
Section: Subdural Electrodesmentioning
confidence: 99%
“…24 Other factors affecting postoperative outcome include focal onset of ictal activity as captured within the margins of the SDEs, and completeness of resection of the epileptogenic zone. 22 In fact, one study has suggested improved outcomes when the ictal onset electrode sites are resected, and also the regions of early spread (as defined by EEG activation within 5 seconds of ictal onset). 25 SDEs also permit extraoperative functional mapping of motor and speech/language sites, with excellent outcomes for localizing eloquent brain tissue that is spared at the time of resection.…”
Section: Subdural Electrodesmentioning
confidence: 99%